Online Shopping and Customer Satisfaction in College–Level Students in Kathmandu Valley - Manandhar, Raju Bhai; Timilsina, Jagat (Journal of Business and Management, 2023)
Background: Online shopping is becoming a popular electronic business day by day even in. Consumers can directly buy goods or services through the internet using a web browser when they engage in online shopping. Objectives: The primary objective of the study is to investigate how factors such as product quality, information accessibility, and shipping costs affect customer satisfaction toward online shopping in Kathmandu Valley. Methods: The study used an analytical research design. By utilizing a convenience sampling technique, 400 respondents were chosen from college-level students in Kathmandu Valley. The questionnaire survey was used to gather the primary data, which was then analyzed using cross-tabulation, an independent t-test, correlation analysis, and regression to produce the study’s findings. Results: There is an association between information availability, product quality, and shipping cost with customer satisfaction toward online shopping, however, there is a strong association between the information availability and customer satisfaction. Customer satisfaction was highly impacted by the product quality and information availability, whereas it was not affected by the shipping cost. The quality of the product, the availability of information, and customer satisfaction were not impacted by gender; only shipping costs were affected. Conclusion: In conclusion, the online company needs to provide accurate information about their products and their business to draw potential customers and maintain the standard of websites with up-to-date information to retain regular customers. The company also needs to sell a high standard of its products and services to improve the company’s reputation to fulfill customers’ expectations. The company should also consider providing better service by timely delivering items at low cost. Future researchers will have access to a larger sample size across a variety of geographic concentrations to evaluate customer satisfaction in online shopping together with other independent factors of the general public.